2023
DOI: 10.3390/jcm12010394
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression Levels in Parents after Counselling for Fetal Heart Disease

Abstract: The progress in fetal cardiology allows for the early diagnosis of congenital heart defects, but there is still a lack of data on the psychological situation of parents expecting a child with a congenital heart defect. In this cross-sectional study, 77 parents (45 women and 32 men) expecting a child with a heart defect were interviewed with different questionnaires. The standardized Hospital Anxiety and Depression Scale (HADS) questionnaire was used to assess the psychological state of the parents. Various sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…False-positive results are a known limitation of F-echo [ 16 ]. Increased maternal anxiety due to a fetal diagnosis of CHD is well reported and thus a false-positive F-echo would be a negative experience for the family [ 32 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…False-positive results are a known limitation of F-echo [ 16 ]. Increased maternal anxiety due to a fetal diagnosis of CHD is well reported and thus a false-positive F-echo would be a negative experience for the family [ 32 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The predictive model of the heart problem and treatment dimension shows a negative effect of the following independent variables: being a 5-to 7-year-old patient with a ToF conduit or UVH diagnosis, with mothers suffering from mild and moderate depression levels. Some studies (Brandt et al, 2023;Erbas et al, 2023) have observed that mothers of children treated at an intensive care unit due to congenital heart disease are at increased risk for the development of depression and di culties in different aspects of postpartum bonding.…”
Section: Discussionmentioning
confidence: 99%